Voatinggine and tabertinggine, pentacyclic indole alkaloids derived from an iboga precursor via a common cleavamine-type intermediate - Kam, T.S.; Nge, C.E.; Gan, C.Y.; Low, Y.Y.; Thomas, N.F. (American Chemical Society, 2013)
Two new indole alkaloids, voatinggine (1) and tabertinggine (2), which are characterized by previously unencountered natural product skeletons,were isolated from a Malayan Tabernaemontana species. The structures and absolute configuration of these alkaloids were determined using NMR and MS analysis, and X-ray diffraction analysis. A possible biogenetic pathway to these novel alkaloids from an iboga precursor, and via a common cleavamine-type intermediate, is presented.